Early Cretaceous Ostracoda (Crustacea) from south-central Araripe Basin, Brazil, with descriptions of seven new species - Tomé, Maria Emilia; Araripe, Rilda; Oliveira, David; Barreto, Alcina; Prado, Ludmila; Pedrosa, Flavia; Pereira, Priscilla; Nascimento, Luiz Ricardo; Ng, Christiano (Zootaxa, 2022)
A systematic study is made of Early Cretaceous (late Aptian/earlyAlbian) ostracod assemblages from the Santo Antônio section. This section is characterized by sediment belonging to the post-rift sedimentary sequence of the Romualdo Formation in the southern-central region of the Araripe Basin, Brazil and represents on of the first marine ingression in the interior of the continent, during the beginning of the formation of the Atlantic Ocean. The Santo Antonio section presents ostracods in greater diversity than previously known. Nineteen samples were analyzed, yielding a total of 8,370 specimens. Fifteen taxa were identified, including six brackish ostracods: Pattersoncypris salitrensis, Pattersoncypris angulata, Pattersoncypris micropapillosa, Damonella grandiensis, Alicenula cf. leguminella and Theriosynoecum cf. quadrinodosum; and nine typically brackish-marine species, including seven new ones: Dicrorygma cf. minuta, Dicrorygma (Orthorygma?) dimorpha, Mongolianella aptianensis sp. nov., Mantelliana speculum sp. nov., Paracypris undulareventralis sp. nov., Microceratina retangularis sp. nov., Perissocytheridea oculusutilis sp. nov., Perissocytheridea poruslinearis sp. nov. and Perissocytheridea florisdorsalis sp. nov. Therefore, the detailed taxonomic study brings a new understanding of marine ostracods around the upper Aptian/lower Albian boundary of the Araripe Basin.